Bobath And Pilates Therapy On Sitting And Standing Balance In Children With Cerebral Palsy - Suharto Suharto; Sri Saadiyah L; Hasnia Ahmad; Tiar Erawan (CV. Inara, 2024)
Cerebral Palsy is the most common neurological disorder in children that affects movement and posture due to damage to the brain which controls motor skills, causing balance problems when sitting and standing. This balance is affected by the strength of the erector spine and abdominal muscles that straighten and control the trunk. If low trunk muscle tone causes problems with balance and mobility so that the child has difficulty sitting, playing in a sitting position, functional hand movements such as eating and activities of daily living. This research is an experiment with a pre test – post one group design which aims to analyze the effectiveness of bobath and pilates therapy on sitting and standing balance in children with cerebral palsy. A total of 17 children with cerebral palsy were given bobath and pilates therapy for 16 weeks, with a dose of: 1 time/day, 3 times a week with a treatment time of 45 minutes for each child. The research subjects were children with cerebral palsy with the following criteria: 1-year old, unbalanced sitting and standing. It will be carried out from February to June 2023. Sitting balance is measured with a sitting level scale and standing balance with a pediatric balance scale. The research subjects consisted of 13 men (76.47%) and 4 women (23.53%) with the GMFCS categories being III and IV. The average age of research subjects: 36.5758 ± 15.02504. The results of statistical tests with Wilcoxon obtained a value of p = 0.001 at the sitting level of the scale and p = 0.002 on the pediatric balance scale. Conclusion: Bobath and pilates therapy are effective in increasing the value of the sitting level of the scale and the pediatric balance scale in children with cerebral palsy.